Via de duplo sentido: Araxá cidade-balneário 1920-1940 - Lima, Glaura Teixeira Nogueira (2007)
The proposal of this thesis is to analyze the formation of Araxá, Minas Gerais, as a bathing city. What was drawn in this path, between 1920 and 1940, with some incursions in the previous decades, was the search for the possibilities of building an ideal model of watering resort. Although distanced geographically, the spaces of the city and of its bathing establishment were united by intense spatial , social and cultural relationships. To this effect, we will discuss some of the forms assumed by the interventions carried out depending on the use of the spaces in those two territories, born around the urban representations, discursive practices and others assumed by segments that lived this daily life, in it working, surviving, reposing or undergoing the treatments through the waters and the thermal mud. Public and private spaces, created and recreated in a politicized atmosphere, pointed out for the guarantee of a cure, rest and summer vacation resort where intense socialization reigned. The subject supposed to be indispensable the one of harmonic functioning amongst body and society has come to reveal others, ramifications of such subject, as the one regarding the senses of the baths and the aesthetic beauty, seeking, in its turn, to consolidate the mythicized trend of the seasons, in particular. The idealized version of the larger and most beautiful mineral watering resort in the continent , conquered with the implantation of the Thermal Compound of Barreiro de Araxá, was inserted in the project of the New State. The meaning of the materialization of this emblematic territory was configured as an attempt to recreate the city itself. Looking for unicity within a multiple scenario, the social relationships maintained in this time of discoveries, euphoria and displeasures, experienced in a wide space of magic representations, built identities and memoirs. Approaching social and cultural subjects, and touching other policies, this theory is centered in abundant textual, visual, oral and material documentation. The diversification of the historical sources or evidences - making possible the work with printed documents, official and non-official manuscripts, pamphlets, newspapers, magazines, daily newspapers, thermal and tourist guides, maps, urban projects, pictures, films, videos, monuments erected in the urban space and oral testimonies - allowed to enlarge the possibility to produce new questionings, new visions